Climate projections over the Antarctic Peninsula region to the end of the 21st century. Part II: wet/dry indices - Chyhareva, A.; Krakovska, S.; Pishniak, D. (Ukrainian Antarctic Journal, 2019)
Objective of the study is an assessment of possible climate change in the region of the Antarctic Peninsula from 1986 until the end of the 21st century projected by the RCMs’ ensemble. During the last decades Antarctica has undergone predominantly warming, with the highest rate of surface air temperature increase found over the Antarctic Peninsula, where the Ukrainian Antarctic Akademik Vernadsky station is located. There is a unique ecosystem in the region which is vulnerable and under the growing impact of a changing weather regime due to rapid climate changes with consequent changes in sea ice, land distribution under snow/ice, etc. Thus, an important task for the region is an estimation of climate change trends and definition of possible subregionalization. Data and methods. Data of two regional climate models HIRHAM5 and RACMO21P forced by two global climate models EC-EARTH and HadGEM from the Polar-CORDEX (Coordinated Regional Downscaling Experiment - Arctic and Antarctic Domains) as part of the international CORDEX initiative were used in the study. Spatial distribution of the model output is 0.44°. Set of scripting codes developed by Climate4R project (An R Framework for Climate Data Access and Postprocessing) was modified in order to extract data for the Antarctic Peninsula region from the Antarctic domain and obtain climatological characteristics for individual RCMs and their ensemble mean. Projected changes in wet/dry climate indices for scenarios RCP4.5 and RCP8.5 for two periods 2041—2060 and 2081—2100 were assessed with respect to the historical experiment 1986—2005. Results. An analysis of projected wet/dry climate indices for both RCP4.5 and RCP8.5 scenarios is presented in Part II of the paper. An analysis of the cold temperature indices (FD, ID) is presented in Part I of the study. In the historical experiment Larsen Ice Shelf and leeward east coast are the regions with the lowest total precipitation in wet days (PRCPTOT, 200—300 mm) and simple daily intensity index (SDII, about 5 mm/day) with under 10 days of consecutive wet days (CWD) and up to 30 days consecutive dry days (CDD). In the cross of the 21st century, duration of dry spell is projected to shorten for the whole peninsula and for Akademik Vernadsky station by about 7—10% under the scenario RCP4.5 and 10—15% under the RCP8.5. Projected SDII changes are up to +20% till the end of the century under the scenario RCP8.5 at north-west coast of the Antarctic Peninsula. Conclusions. Over the Antarctic Peninsula region both scenarios project an average increase in total PRCPTOT and SDII; overall the maximum length of CWD is extended while the maximum length of the CDD is reduced. In combination with decreasing number of frost (FD) and ice (ID) days, the pattern of changes differs notably across the peninsula. It is shown in the first part of the paper that over the Antarctic Peninsula region, both scenarios project an average decrease in the cold season period. The most pronounced changes of ID and FD climate indices are for the Larsen Ice Sheet area. Analyzing results presented in both parts of the paper we can distinguish a few subregions with different projected changes in climate conditions based on obtained climate indices. Obtained results can be used for studies of the climate changes impact on ecosystems in the region and for the strategic planning of future activities (scientific, touristic, fishery, etc.).